Performance of tramadol drug as a safe inhibitor for aluminum corrosion in 1.0 M HCl solution and understanding mechanism of inhibition using DFT - M. Abdallah; E.A.M. Gad; M. Sobhi; Jabir H. Al-Fahemi; M.M. Alfakeer (Egyptian Journal of Petroleum)
The inhibitory effect of tramadol drug (TR) on aluminum (Al) corrosion was demonstrated in 1MHCl solution by weight loss, galvanostatic, potentiodynamic anodic polarization, electrochemical impedance measurements. The inhibition of drug TR is increased with increased concentration and minimize temperature. Data obtained from the polarization mention that TR drug is a mixed inhibitor mainly anodic (βa > βc). The inhibition power of TR drug was explained on the basis of its adsorption on the Al surface and the pitting corrosion of Al is lowered by adding TR drug. Density functional theory (DFT) was utilized to interpret the inhibiting action of TR drug. Some quantum chemical descriptors were carried out. The result of computational calculations of the specifications proves that the address molecule acts as corrosion inhibitors. Keywords: Tramadol drug, Corrosion inhibitors, Adsorption, DFT, Quantum chemical descriptors, Fukui function